The population structure and genetic diversity of Listeria monocytogenes ST9 strains based on genomic analysis - Song, Zexuan; Ji, Shunshi; Wang, Yan; Luo, Lijuan; Wang, Yiqian; Mao, Pan; Li, Lingling; Jiang, Huaying; Ye, Changyun (Frontiers in Microbiology, 2022)
Listeria monocytogenes is a ubiquitous foodborne pathogen causing both invasive and non-invasive listeriosis. Sequence type (ST) 9 is common in food and food processing environment. In this study, the whole-genome sequences (WGS) of 207 ST9 isolates from different sources, geographical locations (14 countries) and isolated years were analyzed. The ST9 isolates were divided into three clusters by phylogenetic analysis, 67.63% of ST9 isolates contain putative plasmids with different size and genomic structure, the putative prophages inserted in chromosome at ten hotspots, seven types of premature stop codon (PMSC) mutations in inlA were found in 81.86% of the ST9 isolates. In addition, 78.26% of ST9 isolates harbor Tn554-like element carried arsenic resistance genes. All the ST9 isolates conservatively contain environment resistance genes on chromosome. The analysis of population structure and feature of ST9 isolates would be helpful to develop effective strategies to control this prevalent pathogen in food chain.